Research progress on Haemophilus parasuis vaccines - Duan, Yu; Hao, Yue; Feng, Huapeng; Shu, Jianhong; He, Yulong (Frontiers in Veterinary Science, 2025)
Haemophilus parasuis (HPS) is the causative agent of porcine Glässer’s disease, which has become prevalent in China in recent years. It is characterized by fibrinous polyserositis, arthritis, and meningitis, but often shows mixed infection with other upper respiratory tract pathogens, causing heavy economic losses to the pig industry. Vaccination is an important means to prevent and control HPS infection, and the currently available vaccines are mainly the inactivated type or subunit vaccines containing immunogenic HPS proteins. This study reviews recent advances in HPS vaccines, analyzes the relative effectiveness of the components of subunit vaccines and discusses the advantages and disadvantages of each vaccine type. The goal is to provide insights for the development of more effective vaccines against Haemophilus parasuis infections in pigs.